Toxicodynamic insights of 2C and NBOMe drugs – Is there abuse potential? - Eva Gil-Martins; Daniel José Barbosa; Fernanda Borges; Fernando Remião; Renata Silva (Toxicology Reports)
Drug use represents a prevalent and multifaceted societal problem, with profound implications for public health, social welfare, and economic stability. To circumvent strict international drug control regulations, there is a growing trend in the development and market introduction of novel psychoactive substances (NPS), encompassing a wide range of compounds with psychoactive properties. This includes, among other classes of drugs, the phenethylamines. Originally derived from natural sources, these drugs have garnered particular attention due to their psychedelic effects. They comprise a broad spectrum of compounds, including 2,5-dimethoxyphenylethylamine (2C) drugs and their corresponding N-(2,5-dimethoxybenzyl)phenethylamine (NBOMe). Psychedelics are conventionally perceived as having low addiction potential, although recent reports have raised concerns regarding this topic. These substances primarily interact with serotonin receptors, particularly the 5-HT2A subtype, resulting in alterations in sensory perception, mood, and introspective experiences. In addition to their psychedelic properties, 2C and NBOMe drugs have been associated with a multitude of adverse effects, such as cardiovascular complications and neurotoxicity. This manuscript provides a comprehensive review of the psychedelic pathways underlying 2C and NBOMe designer drugs, focusing on their interactions with serotonergic and other neurotransmitter systems, shedding light on their potential for abuse.